An analysis of the effect of the bow entrance angle on ship resistance - Andi Trimulyono; Muhammad Iqbal; S. Samuel; Sam Timoty Frans Evan S. (SINERGI, 2022)
Modifying the hull shape is one of the challenges in designing a ship. The angle of the ship's entrance is a significant determinant of the total resistance of the ship. This research aimed to analyze the total resistance of the ship due to changes in the shape of the ship's bow. This research used the Computational Fluid Dynamics (CFD) method with overset mesh technique to predict the ship's total resistance and trim angle. Parameters used in the five-speed numerical simulations. This research indicated that a change in the bow angle of the ship results in a 5% change in the ship's resistance for every change in the bow entrance angle. Therefore, the prediction of total resistance shows significant results in planning conditions. Compared to another bow entrance angle at low Fr, total resistance has no noticeable differences. Angle changes of the entrance of the ship's bow also significantly affected the trim conditions on the ship according to the speed. At Fr 1.03, the stern trim angle tended to decrease dramatically. As a result, the trim by stern under porpoising probably oscillates considerably.